ACDV, Association Chimie du Végétal : une initiative française pour développer la chimie du végétal - Friès Aurore (Oléagineux, Corps gras, Lipides, 2013)
Industry dependence on external fossil fuel resources, fluctuations in energy and raw materials costs, climate change, environmental regulations, changing consumer attitudes etc. In France, where agriculture and the chemical industry are two pillars of the economy, these harsh realities have prompted the chemical and agro-resources sectors to look to biobased chemistry as a means of diversifying outlets for biomass and chemical sourcing, with the aim of balanced use. French players in this international sector have realised the value of joining forces, pooling skills, knowhow and resources into a single structure to drive forward the development of biobased chemistry. This shared vision and determination resulted in the creation in 2008 of the French biobased chemistry association, Association Chimie du V_eg_etal (ACDV). This initiative, still the first of its kind, brings together within a single federation all those directly involved in biobased chemistry. ACDV’s stated aim: to propose and create industrial, economic and political conditions conducive to the development of this industrial reality, within a context of competitive, responsible and sustainable agricultural and chemical sectors. ACDV acts as a source of creative ideas, presenting national and European bodies with the strategic vision and position of French industrialists as regards the international development and competitiveness of biobased chemistry. A commitment by the French chemicals industry to a target of 15% biobased raw materials by 2017 is one of the key factors underpinning the work of the ACDV.